The Archetypal Analysis on Main Characters of Stephen King's Rita Hayworth and Shawshank Redemption - Thesalonika Alvina; Mike Wijaya Saragih (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2023)
This research article explores the application of Jungian archetypal theory in analyzing Stephen King's novella, Rita Hayworth and Shawshank Redemption. The primary focus of this analysis is to uncover the archetypal identities embodied by the central characters, Andy Dufresne and Ellis "Red" Redding. Employing a close-reading method, the researcher examines the novella to gather relevant data for this study. By delving deep into their individual journeys and psychological transformations, the objective of this research is to unveil the underlying archetypal forces that shape their roles within the narrative. Drawing inspiration from Carl Jung's concept of archetypes and the collective unconscious, this analysis identifies Andy Dufresne as a manifestation of the "trickster" and "hero" archetypes, as evidenced by his portrayal in the story. On the other hand, Red embodies the "mentor" archetype, serving as a seasoned inmate and the narrator of the novella. In this way, the study sheds light on the archetypal dimensions present in the characters of the novella.